2023
DOI: 10.3346/jkms.2023.38.e22
|View full text |Cite
|
Sign up to set email alerts
|

Immunogenicity of SARS-CoV-2 Vaccine in Kidney Transplant Recipients: A Cross-Sectional Study in Korea

Abstract: Eighty-five Korean kidney transplant recipients who received three doses of severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) vaccine were tested with anti-receptor binding domain (RBD) antibody and neutralizing antibody. High anti-RBD antibody (≥ 100 U/mL) and neutralizing antibody responses (≥ 30%) were detected in 51/85 (60.0%) patients. When we divided the patients with the time from transplantation to vaccination (< 1, 1–2.4, 2.5–4.9, and ≥ 5-year), anti-RBD antibody titers were 3.2 U/mL, 27.8 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 23 publications
0
4
0
Order By: Relevance
“…The primary cause of this phenomenon would be impaired helper T-cell function of solid organ transplant recipients (positive rate 13/29, 44.8%) and decreased B-cell count and/or function among patients with hematologic malignancies (positive rate 5/25, 20.0%). While previous studies regarding the Korean population mostly focused on poor COVID-19 vaccination response in solid organ transplant recipients, 14 15 our study demonstrated poor nucleocapsid antibody response upon natural infection as well. IGRA showed poor sensitivity due to overlapping distribution between COVID-19 patients and non-infected individuals as well as declining T-cell response to nucleocapsid protein upon time.…”
mentioning
confidence: 48%
“…The primary cause of this phenomenon would be impaired helper T-cell function of solid organ transplant recipients (positive rate 13/29, 44.8%) and decreased B-cell count and/or function among patients with hematologic malignancies (positive rate 5/25, 20.0%). While previous studies regarding the Korean population mostly focused on poor COVID-19 vaccination response in solid organ transplant recipients, 14 15 our study demonstrated poor nucleocapsid antibody response upon natural infection as well. IGRA showed poor sensitivity due to overlapping distribution between COVID-19 patients and non-infected individuals as well as declining T-cell response to nucleocapsid protein upon time.…”
mentioning
confidence: 48%
“…Recently transplanted SOTRs usually require high-intensity immunosuppression, a known risk factor associated with weak responses to vaccinations, including the COVID-19 vaccine [ 48 , 49 , 50 ]. A German study of KTRs who were transplanted recently (with transplant vintage median of 2 years) and on more intense immunosuppression (77.8% of patients were on a triple therapy of tacrolimus, MMF, and prednisone) had a low seroconversion rate of 34.48% (10/29) after the third mRNA vaccine [ 51 ]. Similarly, a cross-sectional study showed that KTRs with a higher transplant vintage had better responses to vaccination than those recently transplanted [ 52 ].…”
Section: Immunosuppression and Vaccine Response In Solid Organ Transp...mentioning
confidence: 99%
“…However, only 27% achieved high titers (defined in this study as 4160 AU/mL), compared to 93% in healthy controls [ 64 ]. Another study investigated the third or fourth dose of the mRNA vaccine mRNA-1273 (Moderna, CA, USA) in 36 KTRs, showing a poor seroconversion rate of only 34%, with no KTRs developing neutralizing antibodies to the Omicron variant BA.1 [ 51 ].…”
Section: Vaccine Boostersmentioning
confidence: 99%
“… 11 An extended half-life was obtained by reengineering Fc variant amino acids, and therefore it could be used for pre-exposure prophylaxis in addition to early outpatient treatment, especially for poor vaccine responders such as organ transplant recipients or patients with hematologic malignancies. 11 12 13 14 15 16 Despite mild to moderate decrease of antiviral activity against early omicron sublineages, including BA.1, BA.2, BA.4, and BA.5, it could be used during the omicron dominated outbreak period of 2022, by increasing dosage from 300 to 600 mg. 1 8 As it would not be feasible to perform neutralizing tests against all the newly emerging strains of live viruses, the manufacturer utilized VLP assay to reflect mutations of spike proteins. 6 However, unlike VLP assay result that exhibited moderately decreased activity to BN.1, similar with BA.5, tixagevimab/cilgavimab was not active against BN.1 in the present analysis.…”
mentioning
confidence: 99%